The Use of Encompassing Tests for Forecast Combinations - Kisinbay, Turgut (Washington, D.C. : International Monetary Fund, 2007)
The paper proposes an algorithm that uses forecast encompassing tests for combining forecasts. The algorithm excludes a forecast from the combination if it is encompassed by another forecast. To assess the usefulness of this approach, an extensive empirical analysis is undertaken using a U.S. macroecoomic data set. The results are encouraging as the algorithm forecasts outperform benchmark model forecasts, in a mean square error (MSE) sense, in a majority of cases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Algorithm Forecast; Data Set; Null Hypothesis; Simple Average; WP; United States